Community Service: Branding Strengthening and Digital Marketing Management of Cireng And Ulen Products as a Culinary Identity in Rw 11, Cipanjalu Village, Cilengkrang District: Pengabdian - Ismawanti, Resty (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to identify strategies for strengthening branding and digital marketing management for cireng and ulen products, the culinary identity of Cipanjalu Village, Cilengkrang District. The research method used was a qualitative case study with a triangulation of sources and methods. Data were collected through in-depth interviews, participant observation, and documentation. The results showed that before the intervention, product branding was still weak, evident in inconsistencies in logos, packaging, and brand narratives. The majority of business owners had not yet optimally utilized digital marketing, still relying on conventional methods. The mentoring program included the creation of new logos and packaging, tagline determination, digital content creation training, and the use of social media such as Instagram, Facebook, and WhatsApp Business. A storytelling strategy was used to strengthen consumers' emotional connection with the product. After the intervention, there was an average increase in sales of 35% in three months, an increase in repeat purchases, and a threefold increase in social media followers. Supporting factors for success included collaboration among business owners, support from the village government, and a commitment to maintaining product quality. This study recommends the formation of a community of village culinary entrepreneurs, ongoing training, and the development of collective digital promotions as sustainability strategies. The results of this study can be used as a model for developing local products in other areas with similar characteristics.